Co-Current Apparatus for Gas Purification from SO2 - Boyadjiev, Christo; Boyadjiev, B.; Doichinova, M.; Popova-Krumova, P. (Recent Innovations in Chemical Engineering, 2015)
A new patent co-current apparatus for gas purification from SO2 is presented. In comparison with the counter-current gas absorbers the gas velocity in the co-current apparatus increases 5-6 times and as a result the column diameter decreases more than 2 times. The new approach for modeling of the column apparatuses is used for modeling the SO2 absorption in the co-current apparatus. The convection-diffusion model for qualitative analysis and process mechanism identification is used. The average concentration model for quantitative analysis is presented.
Keywords: gas purification